Efeito da simpatria sobre a diversidade genética de Aegla platensis (Crustacea, Decapoda) - Machado, Jober Vanderlei de Vargas (2012)
Sympatry is characterized by the existence of two or more species phylogenetically related occupying the same ecological niche. This event has already been recorded in species of crabs of the genus Aegla in Brazil between two species, and though morphological characteristics only. For Aegla, as in most crustaceans, there are few studies to verify if there is any relationship between sympatry and genetic diversity of populations living in this association. In the present study, besides a new record of sympatry between two species of Aegla for Brazil, Aegla platensis and Aegla spinipalma, occurring in Batú River, the occurrence of sympatry among three species, A. platensis, Aegla sp. (in preparation) and Aegla grisella, living in Cambará River, is also presented. To verify the existence of sympatry at the sampling points, besides the morphological characteristics used for the identification of individuals, the technique of DNA-Barcoding was applied using a fragment of 207 bp of the gene COI amplified in 22 individuals and from these sequences interspecific, intra- and interpopulation p-distance values were obtained. Sympatry between two species in Batú River was verified by both morphological and molecular data. For the species living in Cambará River mitochondrial and morphological data were not completely congruent, because some sequences of A. grisella clustered with individuals of other species, presenting low values of interspecific distance. However, these sequences probably are nuclear pseudogenes and when they were removed from the analysis, three species were identified in Cambará River. To verify if there is any relationship between sympatry and genetic diversity of A. platensis, two populations living in sympatry (Cambará and Batú rivers) and one allopatric population from Fiuza River were used. The technique of AFLP was applied to 120 individuals (20 from each population) revealing a high genetic variability for all populations and no relationship between sympatry and level of genetic diversity was found in A. platensis. A high population structuring was observed among populations, which is probably due to the distance among populations and to the low dispersion capability in aeglids. Results from the COI mitochondrial data and from the AFLP nuclear data presented some incongruence when compared, since using AFLP all the A. platensis populations and also the other species were separated through Bayesian analysis and UPGMA, but the same was not found for COI data. The incongruence between mitochondrial and nuclear data reinforces the idea that some A. grisella sequences are in fact nuclear pseudogenes co-amplified in PCR, due to the utilization of degenerated universal primers.